America first : Roosevelt vs. Lindbergh in the shadow of war - Brands, H. W. (Doubleday, a division of Penguin Random House LLC, 2024)
"Bestselling historian and Pulitzer Prize finalist H. W. Brands narrates the fierce debate over America's role in the world in the runup to World War II through its two most important figures: President Franklin D. Roosevelt, who advocated intervention, and his isolationist nemesis, aviator and popular hero Charles Lindbergh. Hitler's invasion of Poland in September 1939 launched a momentous period of decision-making for the United States. With fascism rampant abroad, should America take responsibility for its defeat? For popular hero Charles Lindbergh, saying no to another world war only twenty years after the first was the obvious answer. Lindbergh had become famous and adored around the world after his historic first flight over the Atlantic in 1927. In the years since, he had emerged as a vocal critic of American involvement overseas, rallying Americans toward isolationism as the nominal head of the America First Committee. As Hitler advanced across Europe and threatened the British Isles, President Franklin Delano Roosevelt struggled to turn the tide of public opinion. With great effort, political shrewdness and outright deception--aided by secret British disinformation efforts in America--FDR readied the country for war. He pushed the US onto the world stage where it has stayed ever since. In this gripping narrative, H.W. Brands sheds light on a crucial tipping point in American history and depicts the making of a legendary president"--